Propofol or Midazolam for sedation and early extubation following coronary artery bypass graft surgery: Propofol or Midazolam for sedation and early extubation following coronary artery bypass graft surgery - Asad, Hira; Shahid Hussain; Hamid Mahmood; Imran Ali; Imran Hafeez; Rashid Hussain (Medical Journal of South Punjab, 2023)
Objective: to evaluate the efficacy of Midazolam and Propofol for postoperative sedation and early extubation following cardiac surgery.Methodology: Randomized control trial was conducted cardiac anesthesia department of the National Institute of Cardiovascular Diseases in one year duration of 1st February 2018 to 30th January 2019. Study was conducted on ASA 3 who was selected for coronary artery bypass graft surgery. After shifting in ICU patients were divided in two groups by lottery method and study drugs propofol and midazolam were started. Both infusions were terminated after four hours and patients were assessed for extubation. Hemodynamic parameters arterial blood gases and respiratory function was assessed and recorded.Results: The mean time to awakening, time to extubation in midazolam group was 94.11±4.36 minutes, 94.47±6.11 minutes respectively and in propofol group it was 96.58±4.31 minutes, 91.91±3.94 minutes respectively. Difference was statistically significant.Conclusion: Results of our study reveal that there was no difference in both drugs regarding sedation and extubation time; both drugs are safe, effective and useful in patients of coronary artery bypass graft surgery.